Dinamika Urusan Pemerintahan Konkuren pada Pemerintahan Daerah - Muhammad Lutfi Zaki; Lantef Widodo; Fauzan Al Ridwan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to analyze the dynamics of concurrent government affairs in regional governments based on Law Number 23 of 2014 concerning Regional Government. Regional autonomy gives regions the right to manage and regulate their own government affairs, including the division of authority between the central, provincial, and district/city governments. However, the implementation of this division of authority is often faced with challenges, such as conflicts of authority between the central and regional governments, as well as the impact of changes in authority from district/city to province which result in increased budget burdens. This study uses a legislative and conceptual approach, with data collected through literature studies. The results of the study show that although Law Number 23 of 2014 provides a clear legal basis, implementation practices in the field are often not aligned, causing dissatisfaction and slowing down development. Conflicts of authority, unclear division of tasks, and differences in interpretation of regional authority worsen this condition. Therefore, this study suggests the importance of close cooperation between the central and regional governments, as well as the need for clearer and more uniform guidelines in policy implementation, in order to realize an effective and efficient government system.